ANALISIS WACANA KRITIS BUDAYA LITERASI MELALUI APLIKASI WEBTOON BERBASIS MEDIA PEMBELAJARAN INTERAKTIF SEBAGAI UPAYA PENINGKATAN KARAKTER SISWA SEKOLAH MENENGAH - Amin Khudlori; Jutono Gondohanindijo (Universitas Aki, 2020)
One of the successes in high school student learning lies in the use of learning method or model. The development of technology has given great influence on the world of today’s education. Learning media that are independent and technology-based become an attraction for students to improve learning motivation and to educate students to be able to learn independently. This study aims to develop the interactive learning media through webtoon applications as an effort to shape the character of high school students through literacy culture. This research also aims to foster high school students' interest in reading through smart phone technology. The subjects of this study were high school students. The research method used is the method of triangulation which includes data triangulation, triangulation between researchers and theory triangulation. Data collection techniques used in this studywere interviews, observation and documentation. The data obtained were then analyzed using descriptive qualitative analysis techniques. The results of this study are scientific publications and products in the form of interactive learning media in an effort to strengthen the character of high school students. Keywords: Webtoon, literacy culture, character education, interactive learning method